Pharmacological advances of the chlorogenic acids family: current insights and future research directions - Yuan, Qin; Liu, Can; Zhang, Zian; Chen, Fan; Xiao, Qiang; Zhang, Liangqi; Pan, Xue; He, Fuyuan; Xiao, Meifeng (Frontiers in Pharmacology, 2025)
Phenolic acids are considered an important source for developing natural drugs due to their extensive biological activities. The chlorogenic acids (CGAs) family is the most widely distributed botanical drug in the phenolic acid group and is also commonly found in various traditional Chinese medicine (TCM) extracts. The diverse structural variations of naturally occurring chlorogenic acids result in distinct functions and mechanisms. Recent studies have demonstrated that chlorogenic acid can reduce Aβ plaques in Alzheimer’s disease model mice by 37%, indicating its neuroprotective potential. Similarly, CGAs offer protection to the cardiovascular system, gastrointestinal tract, kidneys, and liver, while additionally preventing metabolic syndrome and displaying anticancer and antimicrobial capabilities. The key signaling pathways and factors involved in these effects include PI3K/AKT, NF-κB, JNK, NLRP3, and Keap1/Nrf2. This review, for the first time, provides a comparative analysis of six typical CGAs, systematically reviewing their specific distribution characteristics in traditional Chinese medicinal metabolites, biosynthetic pathways, biological targets, and pharmacological activities. This review provides a reference for the research and rational development and utilization of CGAs.